Transforming the Media Exposure of a City through Star Architecture Projects? - Alaily-Mattar, Nadia; Büren, Nicolas; Thierstein, Alain (Taylor & Francis, 2019)
Can star architecture projects contribute to repositioning their respective cities? Based on the idea that star architecture projects cannot be read at ground level, and instead, the media is their primary site: Image building. This paper focuses on the role that these special projects play in transforming the media exposure of their respective cities. The circulation of the "Bilbao effect" an urban policy in motion, paved the way for this idea; that is, build flagship architecture by a star architect, and thereby disrupt or transform the image of a city. Making use of case studies of three public cultural facilities commissioned to star architects and put into use in three medium-sized European cities in the past ten years, this paper "reads" these projects in the media. It investigates the extent to which a transformation of exposure in the print media has accompanied the development of star architecture projects in their respective cities. Findings regarding quantitative research of selected international and national newspapers and media platforms are presented.
Keywords: Stadtsoziologie; Stadtbild; Stadtimage; Stadtkultur; Medien; Architekt; Architektur; Bauprojekt; Gebäudetyp; Event; Standortmarketing; Stadtmarketing; Fallbeispiel